Bibliometric analysis of STEM-based creative thinking skills in vocational education - Fathimah Al Adawiyyah; Tiara Sekar Harnum; Sintha Wahjusaputri; Abdul Rahman A Ghani (Fakultas Ilmu Pendidikan, Universitas Negeri Yogyakarta, 2026)
STEM-based learning has been widely discussed to support the development of creative thinking skills in vocational education. However, related research remains fragmented and insufficiently synthesized. This study aims to map research trends, pedagogical approaches, and methodological characteristics of STEM-based creative thinking skills in vocational education. A qualitative bibliometric analysis was conducted using performance analysis and qualitative synthesis of publications from 2016 to 2025. Through a multi-stage screening process, 1,360 initial records were refined into eight core articles that met the inclusion criteria, as most studies discussed STEM education, creative thinking, or vocational education separately rather than integratively. The findings indicate that this research field remains emergent, with fluctuating publication trends and geographical concentration primarily in Indonesia. Project-Based Learning (PjBL) was identified as the dominant pedagogical approach, while assessment practices gradually shifted toward performance- and product-based evaluation. This review contributes by providing an integrated synthesis of pedagogical trends, assessment practices, and research gaps related to teacher readiness, methodological diversification, and long-term skill sustainability in vocational education.